Management of Special Transport Processes in the Pharmaceutical Industry - Jałoszyńska-Szych, Beata (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of this chapter is to examine the importance of route optimization in managing the supply chain in the pharmaceutical sector, with particular focus on pharmacy operations. The study adopts a descriptive and analytical approach, based on an analysis of legal regulations and logistics practices. It emphasizes the crucial role of optimization algorithms in planning medicine delivery routes and the need to adapt logistics to dynamic market conditions. The results confirm that the procedures used comply with DPD guidelines and Pharmaceutical Law, and that major wholesalers such as Neuca ensure high-quality transport. Reducing the number of suppliers enables pharmacies to manage supplies more effectively. The study is limited by the local scope of the data analyzed. The findings have practical relevance for pharmacists and pharmaceutical logistics managers. The originality of this chapter lies in its integration of legal, technological, and practical aspects in the context of pharmacy supply chains.